2017
DOI: 10.1108/etpc-05-2017-0066
|View full text |Cite
|
Sign up to set email alerts
|

Sociopolitical testing discourses in elementary teachers’ talk about reading assessment

Abstract: Purpose The purpose of this work is to describe the current sociopolitical context and complex consequences surrounding elementary literacy education in one Midwestern US state and consider how power works through language. Design/methodology/approach Using qualitative methods and critical discourse analysis as a theory and method, surveys and interview data from teachers, administrators and parents, policy documents and other artifacts were analyzed and described to explain the sociopolitical climate. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In this way, tests and examinations help “subjection of those who are perceived as objects and the objectification of those who are subjected.” (Foucault, 1975, cited in McNamara, 2012, p. 565). Such a narrow perspective is propagated through IELTS, Test of English as a Foreign Language (TOEFL), or other English high stakes which award the honor winner medal to native speakers who could win the exclusive proficiency assessment game in their language (Dendrinos, 2013) even though nonnatives are once called proficient they can pass such tests with naturalized discourse (Schmidt, Jacobs, & Meyer, 2017). Given all, these points strengthen the idea that IELTS serves beyond its supposed language testing function and disapproves its being only a general English test (Noori & Mirhosseini, 2021).…”
Section: Contextualizing Decontextualized Language Tests and Their Te...mentioning
confidence: 99%
“…In this way, tests and examinations help “subjection of those who are perceived as objects and the objectification of those who are subjected.” (Foucault, 1975, cited in McNamara, 2012, p. 565). Such a narrow perspective is propagated through IELTS, Test of English as a Foreign Language (TOEFL), or other English high stakes which award the honor winner medal to native speakers who could win the exclusive proficiency assessment game in their language (Dendrinos, 2013) even though nonnatives are once called proficient they can pass such tests with naturalized discourse (Schmidt, Jacobs, & Meyer, 2017). Given all, these points strengthen the idea that IELTS serves beyond its supposed language testing function and disapproves its being only a general English test (Noori & Mirhosseini, 2021).…”
Section: Contextualizing Decontextualized Language Tests and Their Te...mentioning
confidence: 99%
“…One of the major policy issues facing teachers is that of accountability measures in U.S. public schools. Research has shown that the testing culture has an impact on both teaching and learning in literacy classrooms, including text selection, instructional focus, and curricular design (Anagnostopoulos, 2003;Schmidt, Jacobs, & Meyer, 2017). The question is how, and in what ways, teacher education programs are responsive to these challenges and to the shifting practices within K-12 literacy classrooms.…”
Section: Addressing Linguistic Diversity In Teacher Preparationmentioning
confidence: 99%